Separation optimization of long porous‐layer open‐tubular columns for nano‐LC–MS of limited proteomic samples. Issue 17 (4th September 2013) - Rogeberg, Magnus; Vehus, Tore; Grutle, Lene; Greibrokk, Tyge; Wilson, Steven Ray; Lundanes, Elsa; Svec, Frantisek
<x xml:space="preserve">Abstract</x> The single‐run resolving power of current 10 μm id porous‐layer open‐tubular (PLOT) columns has been optimized. The columns studied had a poly(styrene‐co‐divinylbenzene) porous layer (∼0.75 μm thickness). In contrast to many previous studies that have employed complex plumbing or compromising set‐ups, SPE–PLOT‐LC‐MS was assembled without the use of additional hardware/noncommercial parts, additional valves or sample splitting. A comprehensive study of various flow rates, gradient times, and column length combinations was undertaken. Maximum resolution for <400 bar was achieved using a 40 nL/min flow rate, a 400 min gradient and an 8 m long column. We obtained a 2.3‐fold increase in peak capacity compared to previous PLOT studies (950 versus previously obtained 400, when using peak width = 2σ definition). Our system also meets or surpasses peak capacities obtained in recent reports using nano‐ultra‐performance LC conditions or long silica monolith nanocolumns. Nearly 500 proteins (1958 peptides) could be identified in just one single injection of an extract corresponding to 1000 BxPC3 beta catenin (−/−) cells, and ∼1200 and 2500 proteins in extracts of 10 000 and 100 000 cells, respectively, allowing detection of central members and regulators of the Wnt signaling pathway.